Successful Resolution of Nutcracker Syndrome with 3D Printed PEEK Extravascular Stent in an Adolescent Boy - Da-li He; Heng-en Wang; Yong Jiao; Bin Wu; Dong Cui; Yan-yan Li; Yong Yang; Tie-sheng Cao; Vinko Vidjak; Danko Milošević; Bo Zhang (Acta Clinica Croatica, 2022)
Three-dimensional printed polyetheretherketone (PEEK) extravascular stent was applied to treat a 14-year-old boy with nutcracker syndrome. Digital subtraction angiography revealed a segment of the left renal vein (LRV) with reduced contrast filling immediately before its inflow into the inferior vena cava, and high-pressure gradient. The three-dimensional reconstruction model demonstrated that the LRV and the duodenum were contracted at the aortomesenteric angle, resulting in LRV compression from the abnormal high-level duodenal compartment. When duodenum courses between the abdominal aorta and superior mesenteric artery (duodenal interposition), the LRV entrapment occurs even at <90 aortomesenteric degrees. Three-dimensional printed PEEK extravascular stent was chosen to elevate the superior mesenteric artery and lower the duodenum position, thus relieving LRV compression. This extravascular application has significant advantages over open surgery, endovascular stenting and artificial vessel procedures with expanded polytetrafluoroethylene. It provides better cellular vitality by ensuring soft tissue proliferation. By reducing external acceleration and centrifugal force, a three-dimensional printed PEEK extravascular stent reduces adverse side effects. Such a stent has a distinctive personalized design, good stiffness, and durability that allows blood vessel growth, preventing stent migration and thrombosis. Therefore, it is suitable for both adult and pediatric patients. According to the abdominal ultrasound and multi-slice computed tomography scan, the postoperative follow-up results were satisfactory one year after surgery. The patient felt well, the blood flow in the LRV was not obstructed, and the blood flow velocity was average. The external stent was in place.